Assessment of public green spaces’ ecological condition and ecosystem services in Zhodino city - Rondak, Ulyana; Shchasnaya, Irina (Journal of the Belarusian State University. Ecology, 2024)
The article presents the results of public green spaces’ (3 parks, 25 squares, 2 boulevards) ecological condition assessment in Zhodino city (a medium-sized industrial city of oblast subordination in the Minsk region) and calculations of plantings’ ecosystem services. Public green spaces’ ecological condition assessment was carried out in the summer of 2023. In the territory of green spaces, covering an area of 49.71 hectares, there were 30 plots, within which 966 trees, mostly deciduous species, were surveyed. The analysis and assessment of the plantings’ state were carried out based on a set of dendrometric indicators (crown tracery, leaves/needle color, leaves/needle drying, branch drying, mechanical damage, bark abscission) with subsequent calculation of the stand condition index and determination of the category of the plants’ life condition within the established plots. Four categories of their condition were identified: 20% healthy, 30% healthy with signs of weakening, 40% weakened and 10% damaged. Based on information about green spaces’ ecological condition, as well as data on the age and species composition of the plantings, the evaluation of their ecosystem services (integral and elemental) was carried out. Modern concepts of ecosystem services are based on approaches according to which the natural environment functions as a system that brings significant benefits to society, including natural resources. In the Republic of Belarus, the procedure for conducting a cost assessment of plantings’ ecosystem services and determining the cost value of biodiversity for making management decisions in the environmental sphere is defined in TCP 17.02-10-2013 (02120). Calculations conducted in accordance with this document and adapted to identify the services of urban green plantings showed that the integral value of the ecosystem services of public green spaces in Zhodino city is 12,271.3 rubles per year, with parks contributing the most to this amount (8,646.7 rubles per year). The carbon dioxide sequestration volume is 418 tons per year, with park plantings also dominating (281.5 tons per year). The results of the research have allowed recommendations to be made for optimizing the system of public green spaces in Zhodino city.